A study on the determination of the natural park’s sustainable tourism potential - Cetin, Mehmet; Zeren, Ilknur; Sevik, Hakan; Cakir, Cansel; Akpinar, Huseyin (Springer Science and Business Media LLC, 2018)
The surface site of Yesilyuva Nature Park encompasses natural, social, economic, and cultural characteristics and has become a marker of the region's natural and cultural heritage. To support the preservation of this site, promotional activities should be planned. In this study, because of tourism and related opinions of residents and visitors alike in terms of their natural determination, an important cultural and historical feature is aimed at evaluating the tourism potential of Yesilyuva Nature Park. This framework is designed to establish prospective tourism sustainability. As a result, Yesilyuva Nature Park's natural and cultural properties have been determined to be suitable for sustainable tourism activities using geographic information systems (GIS). This protection in the field, which balances sustainability and landscape design, will provide for the development of tourism activities. In the Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis and survey, residents and visitors reported that the most important feature of the Yesilyuva Nature Park was its natural beauty. Visitors often come to observe traditional and natural life and to engage in tourism activities. All the data, which includes maps derived from GIS, represents landscape planning for sustainable tourism areas in Yesilyuva Nature Park.
Keywords: Conservation of Natural Resources; Parks, Recreational; Geographic Information Systems; Prospective Studies; Environmental Monitoring; 11. Sustainability; 8. Economic growth; 15. Life on land; 12. Responsible consumption